Jewish Women Pioneering the Frontier Trail : a History in the American West. - Abrams, Jeanne E., 1951- (NYU Press, 2006)
The image of the West looms large in the American imagination. Yet the history of American Jewry and particularly of American Jewish women--has been heavily weighted toward the East. Jewish Women Pioneering the Frontier Trail rectifies this omission as the first full book to trace the history and contributions of Jewish women in the American West. In many ways, the Jewish experience in the West was distinct. Given the still-forming social landscape, beginning with the 1848 Gold Rush, Jews were able to integrate more fully into local communities than they had in the East. Jewish women in the Wes.